Pattern of anti-diabetic treatment and its relation with glycaemic control among diabetic patients in a tertiary care hospital of Bangladesh - Akter, Nazma (BIRDEM Medical Journal, 2021)
Background: The main determinants of diabetes management, therapeutic habits and glycaemic control are likely to differ between populations. The pharmacological armamentarium to treat hyperglycaemia in type 2 diabetes mellitus (T2DM) has changed substantially over the past few years with the development of new therapeutic agents. This study evaluated relationships between pattern of pharmacological treatment and glycaemic control in patients with T2DM. Methods: This cross-sectional study was carried out among 486 T2DM patients attending the endocrinology outpatient clinic of MARKS Medical College & Hospital, Dhaka, Bangladesh during the period between July 2018 and June 2019. After obtaining written informed consent, both the treatment pattern and the degree of glycaemic control were estimated from T2DM patients. Glycosylated hemoglobin A1C (HbA1c) was determined by liquid chromatography. Glycaermic control categorized as fair control (HbA1c <7.0%), poor control (HbA1c ³7.0%- <9.0%) and very poor control (HbA1c ³9.0%). Results: Out of 486 participants, 65.8% were females. A total 68.1% of the patients were treated with oral antidiabetic drugs (OADs) and 31.9% were treated with both insulin and oral agents. Metformin (92.4%) was the most commonly used OAD; [p=0.01]. Over one fifth (22.1%) were taking combinations of sulfonylurea and metformin [p<0.05] and 19.5% were taking combination of sulfonylurea, metformin and dipeptidyl peptidase- IV inhibitors (DPP4i); [p=0.87]. More than one fourth (25.7%) were treated with two OADs along with insulin; [p=0.05]. In this context, familiar dual OADs combination (14.2%) was metformin and DPP4 inhibitors [p=0.86]. Premixed insulin (17.1%) was the frequently used regimen among different regimen of insulin used in both OADs and insulin group [p=0.22]. More than 50% of the subjects attained fair glycaemic target of HbA1c. But 46.3% accomplished poor and very poor glycaemic control [p=0.08]. Conclusion: The study shows that the proportion of patients treated with only oral diabetic agent was high. In most instances, they were treated with two or three drus combination therapies. The proportion of patients with fair glycaemic control was higher than reports from many countries. Birdem Med J 2021; 11(2): 90-96